2016
DOI: 10.1515/biol-2016-0067
|View full text |Cite
|
Sign up to set email alerts
|

Role and inhibition of Src signaling in the progression of liver cancer

Abstract: During 2012, about 782,500 new liver cancer cases were diagnosed and 745,500 deaths occurred all around the world. Liver cancer is the 2nd major cause of cancer death in men around the world and in underdeveloped countries. Dysregulation of the balance between proliferation and cell death, hepatitis B virus infection and hepatitis C virus chronic infection, and carcinogenic micro RNAs mainly contribute to the development and progression of liver cancer. Under physiological status, Src maintained the foundation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Moreover, Src is also involved in the regulation of invasion and migration in several cancer types [ 81 , 82 ] and the ablation of Src could alternate the CSC phenotype [ 83 ], which is corroborated with our data. Previous studies also reported that dysregulation of Src and GSK3β signaling could mediate cancer progression, metastasis, drug resistance, and ultimately transform into cancer stem cell phenotypes [ 83 , 84 , 85 , 86 ]. Factually, alterations in GSK-3 activity have been explored due to the changes in GSK-3α and GSK-3β phosphorylation at Ser21 and Ser9, respectively, by Akt activation [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Src is also involved in the regulation of invasion and migration in several cancer types [ 81 , 82 ] and the ablation of Src could alternate the CSC phenotype [ 83 ], which is corroborated with our data. Previous studies also reported that dysregulation of Src and GSK3β signaling could mediate cancer progression, metastasis, drug resistance, and ultimately transform into cancer stem cell phenotypes [ 83 , 84 , 85 , 86 ]. Factually, alterations in GSK-3 activity have been explored due to the changes in GSK-3α and GSK-3β phosphorylation at Ser21 and Ser9, respectively, by Akt activation [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking was used to investigate the possibility of interactions between active compounds and key targets ( Chen et al, 2019 ). Then, according to the results of network analysis and the literature, SRC, EGFR, ESR1, PTGS2, and APP were taken as examples ( Liu et al, 2020 ; Yan et al, 2011 ; Markosyan et al, 2019 ; Ren et al, 2016 ; Di Stadio et al, 2017 ). Five key targets were used for molecular docking (the key docking parameters are displayed in Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Network analysis showed that the mechanism for the anti-liver cancer activities of CR-SR, CR, and SR was multi-component, multi-target, and multi-pathway. The results indicated that the key targets of the pathway in cancer were related to the therapeutic effect of anti-liver cancer activities, including SRC, EGFR, ESR1, PTGS2, and APP ( Yan et al, 2011 ; Ren et al, 2016 ; Di Stadio et al, 2017 ; Markosyan et al, 2019 ; Hunter et al, 2020 ; Yuan et al, 2021 ). Specifically, SRC was the non-receptor tyrosine kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is currently one of the most common malignant tumors in the world, and the abnormal regulation of the SPRED protein family is one of the significant changes noted in HCC. 73 For example, the expression of SPRED1 and SPRED2 was found to decrease in 68% of HCC cases, and the overexpression of these SPRED proteins inhibited the proliferation of HCC cells in vitro and in vivo. 16 In addition, the expression level of SPRED proteins in HCC tissues is inversely correlated with the incidence of tumor invasion and metastasis; overexpression of SPRED proteins leads to significant reductions in actin stress fiber formation and cell migration, as SPRED can inhibit the activation of RAF1, which, in turn, inhibits Rho/ ROCK, which regulates these cellular processes.…”
Section: Spred Proteins May Provide New Therapeutic Targets For Hccmentioning
confidence: 97%